2020
DOI: 10.23851/mjs.v30i4.671
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Extended-Spectrum Beta-Lactamases and Metallo-Beta-Lactamase of Multi Drug Resistant Acinetobacter baumannii Causing Nosocomial Infections in Erbil City

Abstract: Background: Resistance to broad‑spectrum beta‑lactams, mediated by extended‑spectrum beta‑lactamases, and metallo‑beta‑lactamase enzymes, is an increasing problem worldwide. The main aim is to study phenotypic characterization of extended‑spectrum beta‑lactamases and metallo‑beta‑lactamase multidrug resistant Acinetobacter baumannii in Erbil City. Materials and Methods: A total of 112 Acinetobacter baumannii isolations were collected from patients of all age groups from clinical specimens sputum, blood, pus, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The result showed that all isolates were insusceptible to the majority of antimicrobials the lower degree of insusceptibility was found in Netilmicin and Tobramycin at 86.367% followed by Tri/sulfamethoxazole at 80.00%, and Tigycycline 18.33%. The sensitivity pattern to Colistin antibiotic was identified in all isolates, our finding of this study agreed with the studies that were done in Erbil 23,24 both studies found most tested samples were sensitive to Colistin, and Polymyxin B. The distribution of samples in this study throughout clinical specimens demonstrated a range of these rates, with sputum 45 (75%) being the major source of Acinetobacter baumannii is anopportunistic nosocomial bacteria.…”
Section: Comparison Of Mic and Mbicsupporting
confidence: 90%
“…The result showed that all isolates were insusceptible to the majority of antimicrobials the lower degree of insusceptibility was found in Netilmicin and Tobramycin at 86.367% followed by Tri/sulfamethoxazole at 80.00%, and Tigycycline 18.33%. The sensitivity pattern to Colistin antibiotic was identified in all isolates, our finding of this study agreed with the studies that were done in Erbil 23,24 both studies found most tested samples were sensitive to Colistin, and Polymyxin B. The distribution of samples in this study throughout clinical specimens demonstrated a range of these rates, with sputum 45 (75%) being the major source of Acinetobacter baumannii is anopportunistic nosocomial bacteria.…”
Section: Comparison Of Mic and Mbicsupporting
confidence: 90%
“…Aucuba, 6-O-phydroxybenzoylmussaenosidic acid, aucuba, 10-pcoumaroylaucubin (eurostoside), aucubin, 6-O-phydroxybenzoylmussaenosidic acid, and aucubin are some of the other iridoids [6]. focused, and the acid mussaenosidic [7].…”
Section: Chemical Structurementioning
confidence: 99%